Why Do They Do It?–A Brief Inquiry into the Real Motives of Some of the Participants in the Recording, Transcribing, Translating, Editing, and Publishing of Aboriginal Oral Narrative - Cardinal, Philippe (TTR)

(untitled) (Association canadienne de traductologie, 2005)
This article inquires into the motives of the participants in the recording, transcribing, translating, editing and publishing of Aboriginal narrative. The motivation of Aboriginal communicators, at the outset simple altruism, has evolved onto a pressing need to bear witness to past and present wrongs perpetrated against them by various agents of the dominant society. Social scientists’ motivations are equally complex. Most of the social sciences, and particularly anthropology, practice translation. Anthropology has elaborated translation theories that betray a general unease with how and why anthropologists translate. Anthropological translation differs from that of other disciplines in that when anthropologists translate oral and written “texts,” their ultimate aim is in fact the “translation” of the cultures that produced them.Keywords: anthropology, translation, Aboriginal, oral narrative, cultures.